A colorimetric sensing platform for the determination of H2O2 using 2D–1D MoS2-CNT nanozymes. Issue 44 (5th October 2022) - Zhang, Xin; Wang, Siqin; Dao, Jiahao; Guo, Jiajing; Gao, Yanfang
Abstract : A novel colorimetric platform based on 2D–1D MoS2 -CNT nanozymes, was fabricated for the selective and sensitive determination of hydrogen peroxide (H2 O2 ) in soda water. Abstract : A novel colorimetric platform based on nano-composites of two-dimensional (2D) molybdenum disulfide nanosheets (MoS2 NSs) and one-dimensional (1D) carbon nanotubes (CNTs), called 2D–1D MoS2 -CNT nanozyme, was fabricated for the selective and sensitive determination of hydrogen peroxide (H2 O2 ) in soda water. The MoS2 -CNT nanozyme was synthesized through a one-step solvothermal reduction method. The introduced CNTs could effectively prevent the stacking of MoS2 nanosheets (NSs) and not only expanded the interlayer distance of MoS2 NSs from 0.620 nm to 0.710 nm but also improved their specific surface. Under acidic conditions, the as-prepared 2D–1D MoS2 -CNT nanozymes could oxidize the colorless 3, 3′, 5, 5′-tetramethylbenzidine (TMB) to blue-oxidized TMB (oxTMB) in the presence of H2 O2, resulting in enhanced peroxidase-like (POD-like) activity. The kinetic study showed that MoS2 -CNT nanozyme had stronger catalytic activity than natural horseradish peroxidase (HRP). The linear range for H2 O2 colorimetric determination was 5.00–500 μmol L −1 with a limit of detection (LOD) of 1.40 μmol L −1 . Furthermore, the established determination method was applied to actual samples and the recoveries of H2 O2 spiked in soda water were in the range of 92.3–107%, showing feasibility for the analysis of food.